2024
DOI: 10.1039/d3sc05613a
|View full text |Cite
|
Sign up to set email alerts
|

Selective poly(vinyl ether) upcycling via photooxidative degradation with visible light

Darren L. Langer,
Sewon Oh,
Erin E. Stache

Abstract: Poly(vinyl ethers) (PVEs) have many applications, such as adhesives, lubricants, and anticorrosive agents, thanks to their elastic, nonirritating, and chemically inert properties. The recycling of PVEs remains largely underexplored, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In 2024, the group of Stache demonstrated the upcycling of poly(vinyl ethers) via a photocatalytic HAT reaction. [31] Based on their previous work on polystyrene upcycling using environmentally-friendly FeCl 3 and FeBr 3 , a similar catalytic system is employed here under visible light irradiation to generate chlorine and bromine radicals, respectively, that can act as HAT agents. Isobutanol, isobutyraldehyde, and isobutyric acid were isolated as high valued small molecules in a yield up to 50 %.…”
Section: Degradation Of Other Vinyl Polymersmentioning
confidence: 99%
“…In 2024, the group of Stache demonstrated the upcycling of poly(vinyl ethers) via a photocatalytic HAT reaction. [31] Based on their previous work on polystyrene upcycling using environmentally-friendly FeCl 3 and FeBr 3 , a similar catalytic system is employed here under visible light irradiation to generate chlorine and bromine radicals, respectively, that can act as HAT agents. Isobutanol, isobutyraldehyde, and isobutyric acid were isolated as high valued small molecules in a yield up to 50 %.…”
Section: Degradation Of Other Vinyl Polymersmentioning
confidence: 99%
“…27−29 Moreover, recent photochemical studies have also demonstrated that halogen radicals can act as the HAT reagent and selectively abstract benzylic hydrogens under mild reaction conditions. 30,31 Regarding the use of light-induced HAT (photo-HAT) reactions in the degradation/valorization of PS derivatives, Hu and Stache groups have efficiently degraded commercial-grade Styrofoam to lower-molecular-weight benzoyl products (benzoic acid, benzaldehyde, and bromoacetophenone) under UV or visible light, using FeCl 2 and FeCl 3 catalytic systems by taking advantage of hydrogen abstraction ability of chlorine radicals (Scheme 1A). 32,33 These methods, which were based on HAT principles, required increased photonic efficiency (flow reactor) and/or solvents for dissolving the metal salts to obtain significant conversion of value-added products.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced methods to degrade waste polymers are sustainable alternatives to thermal methods. , Photochemical treatment of synthetic and natural waste polymers has recently become the main focus of scientists because of the lower energy requirements and greener nature, which meet the criteria of sustainability. , Although hydrogen atom transfer (HAT) reactions have always been a versatile tool for C–H bond chemistry, exploitation of light-induced HAT reactions for the degradation/valorization of waste polymers through oxidative C–C bond breakages has recently proved to be an effective and sustainable strategy. Moreover, recent photochemical studies have also demonstrated that halogen radicals can act as the HAT reagent and selectively abstract benzylic hydrogens under mild reaction conditions. , …”
Section: Introductionmentioning
confidence: 99%